Diversity and Dynamics of Epidermal Microbes During Grape Development of Cabernet Sauvignon (Vitis vinifera L.) in the Ecological Viticulture Model in Wuhai, China - Wei, Ru-teng; Chen, Ning; Ding, Yin-ting; Wang, Lin; Gao, Fei-fei; Zhang, Liang; Liu, Yi-hui; Li, Hua; Wang, Hua (Frontiers in Microbiology, 2022)
Grapevine-related microorganisms affect the health and yield of grapes, the metabolic pathways of the fermentation process, and the regional characteristics of wine. However, the diversity of epidermal microorganisms during the development of berries under the ecological viticulture model has not been described in detail. In this study, high-throughput amplicon sequencing technology was used to perform ITS and 16S sequencing of Cabernet Sauvignon epidermal microbes at different developmental stages in Wuhai region to investigate the succession of epidermal microbes and their response to developmental stages and vineyard weather. The results showed that the diversity of fungi and bacteria decreased during development. Epidermal microorganisms recruited members according to their developmental stages, but retained the core taxa, such as the fungi genera Alternaria, Jattaea, Jattaea, and the bacteria genera Brevundimonas, Sphingomonas, Acinetobacter, Pseudomonas. In addition, the microbial diversity was association with specific meteorological parameters, implying that there was a connection between the environmental conditions of the vineyard and the microbial distribution pattern, such as, the fungi genus Filobasidium was positively correlated with relative humidity, and negatively correlated with average high temperature, average low temperature, and average ground temperature; the bacteria genus Lactobacillus was positively correlated with sunlight time, and negatively correlated with relative humidity. In conclusion, this work can help vineyard managers understand the microbial consortia associated with particular diseases, and also the dynamics of infection processes in order to take preventive actions, especially at the most critical moments.